To find the product of the polynomial expressions \( (xy+1)(x-3) \), we use the distributive property (also called the FOIL method for binomials).
-
Distributing \( xy \) to both terms in \( (x-3) \): \[ xy \cdot x = x^2 y \quad \text{and} \quad xy \cdot (-3) = -3xy \]
-
Distributing \( 1 \) to both terms in \( (x-3) \): \[ 1 \cdot x = x \quad \text{and} \quad 1 \cdot (-3) = -3 \]
-
Now combine all the results: \[ x^2 y - 3xy + x - 3 \]
So the final product is: \[ x^2 y - 3xy + x - 3 \]
Looking at the responses given, the correct answer is: x²y - 3xy + x - 3.